Pengembangan Profesionalisme Guru Melalui Kegiatan Lesson Study di Pondok Pesantren Nurul Haramain Putra NW Narmada : Manfaat dan Tantangannya - Muhammad Amin; Mahyuni Mahyuni; Lalu Jaswadi Putera (PALAPA, 2019)
Due to the dynamic and ever-changing contexts of their work, teachers need to continuously develop their professionalism. One professional development procedure close enough to teachers’ work place, the classroom, is Lesson Study (LS). This paper illustrates the potentials benefits of implementing LS in one Islamic school in Lombok and the challenges of implementing this procedure in this particular school. Data were collected through distribution of questionnaire to 31 teachers of this school. Results of data analysis indicate that all teachers are positive about the advantages of applying LS in their classrooms. However, they are also aware of the potential challenges of implementing this professional development procedure in the school, which needs careful consideration. Following a list of all these challenges is recommendation of how to deal with them.